A CASE DIAGNOSED WITH FOUR DIFFERENT TUMORS - Fatma Tuba YILDIRIM (Elsevier, 2021)
Case report: Chromosomal breakage syndromes are characterized by cancer predisposition. Here we present a 27-month-old female with Fanconi Aplastic Anemia diagnosed with 4 tumors. Imaging showed brain mass causing the shift, liver mass and left kidney mass. She had diagnosed with high grade intracranial tm, wilms tm and hepatocellular ca. Because of refractory pancitopeni, she underwent HSCT. After 2months she developed intracranial embryonal tumor. The patient died with progression. Genetic tests revealed no mutation.